Glass material manufacturing method and glass material
By using lanthanum raw materials with low hygroscopicity and controlling their particle size in the container-free suspension method, the problem of the decline in the yield of glass materials due to the deviation of the mixing components is solved, and the stable manufacturing and quality improvement of glass materials are achieved.
Patent Information
- Application Number
- CN202380051576.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-04
- Filing Date
- 2023-06-27
- Publication Date
- 2025-02-18
AI Technical Summary
In the container-free suspension method, the yield of the glass material is prone to decrease due to slight deviation in the mixing component.
The glass material is stably manufactured by using lanthanum raw materials with low hygroscopicity such as lanthanum hydroxide, lanthanum carbonate, or lanthanum phosphate as raw materials for lanthanum, and controlling the average particle size D50 of the lanthanum raw material to be 50 μm or less.
It effectively suppresses the deviation of the mixing components, ensures the stable manufacturing of glass materials, and improves the yield and quality of glass materials.
Smart Images

Figure CN119486978A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a glass material and the glass material. Background Art
[0002] In recent years, as optical systems used in cameras, microscopes, endoscopes, and the like have become smaller and lighter, optical elements with high refractive indexes have been required.
[0003] The above optical elements are often made of glass materials. In order to increase the refractive index of glass materials, it is necessary to reduce the content of SiO2 and B2O3, which are the main skeleton components of glass, and contain a large amount of rare earth oxides such as La2O3, Gd2O3, and Ta2O5. However, if the skeleton components are reduced, the glass forming ability is likely to decrease, and vitrification is likely to become difficult.
[0004] As one of the methods for producing a glass material having a composition that is difficult to vitrify, a containerless suspension method is known in which a raw material is melted in a suspended state and then cooled (for example, Patent Document 1).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2014-196236 Summary of the invention
[0008] Technical problem that the invention aims to solve
[0009] In the containerless suspension method, there is a problem that the yield of the glass material is easily reduced due to a slight deviation in the blended components.
[0010] In view of the above circumstances, an object of the present invention is to provide a method for producing a glass material and a glass material that can be produced stably.
[0011] Technical solutions to the problem
[0012] A method for producing a glass material and various aspects of the glass material that solve the above-mentioned problems will be described.
[0013] The manufacturing method of the glass material of mode 1 is characterized in that it is a method for manufacturing glass raw material by heating and melting a glass raw material block in a suspended state and then cooling it, and the glass material contains lanthanum, and at least one raw material selected from lanthanum hydroxide, lanthanum carbonate or lanthanum phosphate is used as the lanthanum raw material.
[0014] In the method for producing a glass material according to the second aspect, in addition to the method according to the first aspect, it is preferred that the method further comprises a step of forming a glass raw material lump, and in the step of forming the glass raw material lump, the lanthanum raw material is used.
[0015] In the method for producing a glass material of Embodiment 3, in Embodiment 1 or 2, preferably, the average particle size D50 of the lanthanum raw material is 50 μm or less. It should be noted that the “average particle size D50” is a value measured on a volume basis and refers to a value measured by a laser diffraction method.
[0016] In the method for producing a glass material according to aspect 4, in any one of aspects 1 to 3, the glass material preferably contains 5 to 75% of La 2 O 3 in terms of mol %.
[0017] In the method for producing a glass material of embodiment 5, in any one of embodiments 1 to 4, preferably, the glass material further contains, in mol%, 0% to 40% of B2O3 and 5% to 100% of La2O3+B2O3.
[0018] In the method for producing a glass material according to Embodiment 6, in any one of Embodiments 1 to 5, preferably, the β-OH value is 0.005 mm -1 ~0.3mm -1 The β-OH value is a value obtained by measuring the transmittance of glass using FT-IR and using the following formula (1).
[0019] (1) β-OH value = (1 / X) log (T1 / T2)
[0020] X: Glass wall thickness (mm)
[0021] T1: Reference wavelength 4000cm -1 Transmittance under (%)
[0022] T2: Hydroxyl absorption wavelength 3300cm -1 ~3450cm -1 Minimum transmittance near (%)
[0023] In the method for producing a glass material according to aspect 7, in any one of aspects 1 to 6, preferably, the refractive index nd of the glass material is 1.85 or more.
[0024] The glass material of Scheme 8 is characterized in that it contains 5% to 75% La2O3 in mol% and has a β-OH value of 0.005 mm -1 ~0.3mm -1 The β-OH value is a value obtained by measuring the transmittance of glass using FT-IR and using the following formula (1).
[0025] (1) β-OH value = (1 / X) log (T1 / T2)
[0026] X: Glass wall thickness (mm)
[0027] T1: Reference wavelength 4000cm -1 Transmittance under (%)
[0028] T2: Hydroxyl absorption wavelength 3300cm -1 ~3450cm -1 Minimum transmittance near (%)
[0029] In the glass material of embodiment 9, in embodiment 8, it is preferable to use it in the visible light wavelength region.
[0030] Effects of the Invention
[0031] According to the present invention, a method for producing a glass material and a glass material that can be produced stably can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a schematic cross-sectional view showing one embodiment of an apparatus for producing the optical glass of the present invention. DETAILED DESCRIPTION
[0033] Hereinafter, embodiments of the present invention will be described in detail using the accompanying drawings. However, the present invention is not limited to the following embodiments. In the following description of the content of each component, "%" means "mol %" unless otherwise specified.
[0034] <Method for producing glass material>
[0035] The manufacturing method of the glass material of the present invention is a method for manufacturing the glass material by heating and melting a glass raw material block in a suspended state and then cooling it, characterized in that the glass material contains lanthanum, and at least one selected from lanthanum hydroxide, lanthanum carbonate or lanthanum phosphate is used as the lanthanum raw material.
[0036] Usually, as lanthanum raw material, lanthanum oxide (La2O3) is known. However, the hygroscopicity of lanthanum oxide is high, and it is easy to increase the mass due to the adsorption of moisture in the atmosphere. Such mass increase may become the reason for the deviation of the allocation composition. Especially in the containerless suspension method, the amount of raw materials that can be melted at one time is small, so it is easily affected by the deviation of the adjustment composition. Therefore, by using at least one or more of lanthanum hydroxide, lanthanum carbonate or lanthanum phosphate selected from hygroscopicity as the lanthanum raw material, the deviation of the allocation composition can be suppressed, and as a result, the glass material can be stably manufactured using the containerless suspension method. In more detail, lanthanum hydroxide or lanthanum carbonate are preferably used, and lanthanum hydroxide is particularly preferably used. In particular, lanthanum hydroxide has excellent homogeneity, so it is more effective to suppress the deviation of the allocation composition.
[0037] As the lanthanum raw material, a commercially available product can be used. Alternatively, lanthanum hydroxide can also be produced by adding pure water to lanthanum oxide, maintaining the mixture at 150° C., and then drying the mixture.
[0038] The average particle size D50 of the lanthanum raw material is preferably 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, 10 μm or less, and particularly preferably 5 μm or less. Thus, it is easy to mix the raw materials uniformly. The lower limit is not particularly limited, for example, preferably 0.1 μm or more, 0.5 μm or more, and particularly preferably 1 μm or more.
[0039] Below, refer to Figure 1 A method for producing a glass material will be described.
[0040] Figure 1 1 is a schematic cross-sectional view showing an embodiment of a manufacturing device for glass material. The manufacturing device 1 has a molding die 10. The molding die 10 also serves as a melting container. The molding die 10 has a molding surface 10a and a plurality of gas ejection holes 10b opened on the molding surface 10a. In this way, the raw material block 12, the molten glass, and the glass material can be stably suspended. In addition, a molding die having only one gas ejection hole 10b can also be used. The gas ejection hole 10b is connected to a gas supply mechanism 11 such as a gas cylinder. Gas is supplied from the gas supply mechanism 11 to the molding surface 10a via the gas ejection hole 10b. The type of gas is not particularly limited, and for example, it can be air, oxygen, or nitrogen, argon, helium, carbon monoxide gas, carbon dioxide gas, or a reducing gas containing hydrogen.
[0041] In the manufacturing method of the glass material of the present invention, the glass material can be manufactured as follows. First, a glass raw material block 12 is formed and placed on the molding surface 10a. The glass raw material block 12 may be a material obtained by integrating glass raw material powder by press molding or the like, or a sintered body obtained by integrating glass raw material powder by press molding or the like and then sintering. In addition, a material obtained by cutting or crushing the above-mentioned sintered body may be used as the glass raw material block 12.
[0042] Next, by ejecting gas from the gas ejection hole 10b, the glass material block 12 is suspended on the molding surface 10a. That is, the glass material block 12 is held in a state of not contacting the molding surface 10a. In this state, the laser irradiation device 13 irradiates the glass material block 12 with laser light. Thus, the glass material block 12 is heated and melted to obtain molten glass. Then, by cooling the molten glass, a glass material can be obtained.
[0043] In the melting step and the cooling step, it is preferred to at least continue to eject the gas to suppress the glass raw material lump 12, the molten glass, and the glass material from contacting the molding surface 10a. The heating method is not limited to the method of irradiating with laser light, and radiation heating may be used, for example.
[0044] In the manufacturing method of the glass material of the present invention, the above-mentioned lanthanum raw material is preferably used in the process of forming the glass raw material block. In other words, it is preferred that after the raw material powder of the glass is prepared using the above-mentioned lanthanum raw material, the prepared raw material powder is separated into a predetermined amount to form the glass raw material block. In addition, it is preferred that the sintered body formed by sintering the raw material powder of the glass after integration by press molding or the like is cut or crushed to form the glass raw material block. In this way, it is easy to suppress the deviation of the prepared components in each glass raw material block 12.
[0045] Examples of the material of the forming die 10 include aluminum, aluminum-magnesium alloy, aluminum-silicon alloy, aluminum-magnesium-silicon alloy, aluminum-magnesium-zinc alloy, metallic silicon, stainless steel, duralumin, platinum, platinum-rhodium alloy, tungsten, tungsten alloy, zirconium, titanium, titanium alloy, boron nitride, etc. Among them, aluminum, aluminum-magnesium alloy, aluminum-silicon alloy, aluminum-magnesium-silicon alloy, and aluminum-magnesium-zinc alloy are preferred in terms of corrosion resistance and processability.
[0046] <Glass Material>
[0047] According to the method for producing a glass material of the present invention, a glass material having a β-OH value of 0.005 mm can be produced. -1 ~0.3mm -1 More specifically, the glass material of the present invention is characterized in that it contains 5% to 75% La2O3 by mol% and has a β-OH value of 0.005 mm -1 ~0.3mm -1 The β-OH value is the value obtained by measuring the transmittance of glass using FT-IR and using the following formula (1). Here, X is the glass wall thickness (mm), and T1 is the reference wavelength of 4000 cm -1 Transmittance (%) under T2 refers to the hydroxyl absorption wavelength of 3300cm -1 ~3450cm -1 The minimum transmittance (%) near . A glass material satisfying the following formula has an effect of being able to produce a glass material having desired characteristics without losing clarity.
[0048] (1) β-OH value = (1 / X) log (T1 / T2)
[0049] The β-OH value of glass material is 0.005mm -1 ~0.3mm -1 , preferably 0.005mm -1 ~0.2mm -1 , particularly preferably 0.005 mm -1 ~0.1mm -1 If the β-OH value is too large, it is difficult to obtain a glass material having desired properties. If the β-OH value is too small, the glass material is prone to devitrification.
[0050] The glass material of the present invention preferably contains 5% to 75% of La2O3 in mol%. More specifically, the glass material of the present invention preferably contains 5% to 75% of La2O3, 0% to 40% of B2O3, and 5% to 100% of La2O3+B2O3 in mol%. The reasons for limiting the composition range of the glass material in this way are explained below. It should be noted that in the following description of the content of each component, "%" means "mol%" unless otherwise specified.
[0051] La2O3 is a component that forms the glass skeleton. In addition, it is also a component that increases the refractive index without reducing the transmittance. The content of La2O3 is preferably 5% to 75%, 10% to 70%, and particularly preferably 15% to 63%. If the content of La2O3 is too little, it is difficult to obtain the above effect. If the content of La2O3 is too much, it is difficult to vitrify.
[0052] B2O3 becomes the glass skeleton and is a component that expands the vitrification range. However, if the content of B2O3 is too much, the refractive index tends to decrease. Therefore, the content of B2O3 is preferably 0% to 40%, 5% to 40%, and particularly preferably 10% to 37%.
[0053] The content of La2O3+B2O3 (the total amount of La2O3 and B2O3) is preferably 5% to 100%, 10% to 80%, 15% to 70%. In addition, the content of La2O3+B2O3 is preferably greater than 18%, greater than 25%, greater than 36%, greater than 40% in weight%, and particularly preferably greater than 41%. If the content of La2O3+B2O3 is too small, it is difficult to obtain the above-mentioned effects. It should be noted that from the viewpoint of stabilizing vitrification, the upper limit of the content of La2O3+B2O3 is preferably 100% in weight%, less than 100%, and particularly preferably less than 90%.
[0054] The glass material of the present invention may contain the following components in addition to the above components.
[0055] Nb2O5 and TiO2 are components that have a good effect of increasing the refractive index. In addition, they also have the effect of expanding the vitrification range. The content of Nb2O5+TiO2 (the total amount of Nb2O5 and TiO2) is preferably 0% to 85%, 15% to 80%, and particularly preferably 25% to 75%. If the content of Nb2O5+TiO2 is too little, it is difficult to obtain the above effect. If the content of Nb2O5+TiO2 is too much, it is difficult to vitrify. In addition, the preferred range of each component is as follows.
[0056] The content of Nb2O5 is preferably 0% to 80%, 10% to 75%, and particularly preferably 15% to 70%.
[0057] The TiO2 content is preferably 0% to 85%, 5% to 80%, and particularly preferably 10% to 75%.
[0058] Ta2O5 is a component that has a good effect of increasing the refractive index. However, if the content of Ta2O5 is too high, it is difficult to vitrify, and there is a tendency for the raw material cost to increase. Therefore, the content of Ta2O5 is preferably 0% to 30%, 0% to 20%, and particularly preferably 0% to 10%.
[0059] Gd2O3 is a component that increases the refractive index and improves the stability during vitrification. The content of Gd2O3 is preferably 0% to 30%, 0% to 20%, and particularly preferably 0% to 10%. If the content of Gd2O3 is too little, it is difficult to obtain the above effect. On the other hand, if the content of Gd2O3 is too much, it is difficult to vitrify.
[0060] ZrO2 is a component that increases the refractive index and forms a glass skeleton as an intermediate oxide, so it has the effect of expanding the vitrification range. In addition, it also has the effect of improving chemical durability. The content of ZrO2 is preferably 0% to 20%, and particularly preferably 0% to 10%. If the content of ZrO2 is too little, it is difficult to obtain the above-mentioned effect. On the other hand, if the content of ZrO2 is too much, it is difficult to vitrify.
[0061] SiO2 becomes the glass skeleton and is a component that expands the vitrification range. However, if the content of SiO2 is too much, the refractive index tends to decrease. Therefore, the content of SiO2 is preferably 0% to 20%, 0% to 15%, 0% to 10%, and particularly preferably 0% to 5%.
[0062] ZnO is a component that easily improves the stability during vitrification and chemical durability. However, if the content of these components is too much, the refractive index decreases and it is difficult to obtain the desired optical properties. Therefore, the content of ZnO is preferably 0% to 20%, 0% to 15%, 0% to 10%, and particularly preferably 0% to 5%.
[0063] MgO, CaO, SrO and BaO are components that can easily improve the stability during vitrification and the chemical durability. However, if the content of these components is too much, the refractive index decreases and it is difficult to obtain the desired optical properties. Therefore, the content of MgO+CaO+SrO+BaO (the total amount of MgO, CaO, SrO and BaO) is preferably 0% to 10%, and particularly preferably 0% to 5%. In addition, the contents of MgO, CaO, SrO and BaO are preferably 0% to 10%, and particularly preferably 0% to 5%.
[0064] The refractive index nd of the glass material is preferably 1.85 or more, 1.9 or more, 1.95 or more, 2.0 or more, 2.05 or more, 2.1 or more, 2.15 or more, 2.2 or more, and particularly preferably 2.25 or more. The higher the refractive index nd, the easier it is to facilitate miniaturization of the optical element. Considering the stability of vitrification, the upper limit of the refractive index nd is preferably 2.45 or less, and particularly preferably 2.4 or less.
[0065] When the glass material of the present invention is used for optical purposes, it is preferably used in the near infrared to visible light wavelength region, and is particularly preferably used in the visible light wavelength region. Specifically, it is preferably used in a region with a wavelength of 2500nm or less, 2000nm or less, 1500nm or less, 1200nm or less, 1000nm or less, 800nm or less, and particularly 780nm or less. The lower limit can be set to, for example, a wavelength of 300nm or more, or a wavelength of 400nm or more.
[0066] Example
[0067] Hereinafter, the present invention will be described based on examples, but the present invention is not limited to these examples.
[0068] Tables 1 and 2 show Examples 1 to 6 and Comparative Examples 7 to 12 of the present invention.
[0069] [Table 1]
[0070]
[0071] [Table 2]
[0072]
[0073] Examples 1 to 6 were prepared as follows. First, raw materials were mixed so as to obtain glass compositions shown in Table 1, and glass raw material blocks were prepared. At this time, the following raw materials A and B were used as lanthanum raw materials.
[0074] (1) Lanthanum raw material A: lanthanum hydroxide La(OH)3 stored in the air (average particle size D50: 2.5 μm)
[0075] (2) Lanthanum raw material B: lanthanum carbonate La2(CO3)3·8H2O stored in the atmosphere (average particle size D50: 10 μm)
[0076] Next, the obtained glass raw material block was used to produce a glass material by a containerless suspension method. At this time, 10 batches of glass materials were produced with the same composition, and the glass transition rate was confirmed. Among the 10 batches, the case where the glass transition rate was 100% was marked as ○, the case where the glass transition rate was less than 100% and 70% or more was marked as △, and the case where the glass transition rate was less than 70% was marked as ×.
[0077] In addition, the refractive index nd and β-OH value of the obtained glass material were measured. For the refractive index nd, the glass material was bonded to a soda board substrate with a thickness of 4 to 5 mm, then ground at right angles, and evaluated using a KPR-2000 manufactured by Shimadzu Corporation using the measured value relative to the d line (587.6 nm) of a helium lamp. For the β-OH value, the transmittance of the glass was measured using FT-IR and was obtained using the following formula (1).
[0078] (1) β-OH value = (1 / X) log (T1 / T2)
[0079] X: Glass wall thickness (mm)
[0080] T1: Reference wavelength 4000cm -1 Transmittance under (%)
[0081] T2: Hydroxyl absorption wavelength 3300cm -1 ~3450cm -1 Minimum transmittance near (%)
[0082] In Comparative Examples 7 to 12, glass materials were prepared in the same manner as in Examples 1 to 6 except that the lanthanum raw material C was used.
[0083] (3) Lanthanum raw material C: lanthanum oxide La2O3 stored in the atmosphere (average particle size D50: 40 μm)
[0084] As shown in Table 1 and Table 2, the glass materials of Examples 1 to 6 have a glass transition rate of 100% and a β-OH value of 0.008 mm. -1 ~0.13mm -1 On the other hand, the glass transition ratios of the glass materials of Comparative Examples 7 to 12 were less than 100%. In addition, the β-OH values of Comparative Examples 8, 10, and 11 were 0.003 to 0.004.
[0085] Explanation of symbols
[0086] 1 Manufacturing equipment
[0087] 10 Molding mold
[0088] 10a Molding surface
[0089] 10b Gas ejection hole
[0090] 11 Gas supply mechanism
[0091] 12 Raw material blocks (suspended objects)
[0092] 13Laser irradiation device
Claims
1. A method for manufacturing a glass material, characterized in that: It is a method of manufacturing glass materials by heating and melting glass raw material blocks in a suspended state and then cooling them. The glass material contains lanthanum, As the lanthanum raw material, at least one raw material selected from lanthanum hydroxide, lanthanum carbonate, or lanthanum phosphate is used.
2. The method for producing a glass material according to claim 1, wherein: The manufacturing method further includes the step of forming a glass raw material block. In the step of forming the glass raw material lump, the lanthanum raw material is used.
3. The method for producing a glass material according to claim 1 or 2, wherein: The average particle size D50 of the lanthanum raw material is 50 μm or less.
4. The method for producing a glass material according to claim 1 or 2, wherein: The glass material contains 5% to 75% La2O3 in mol%.
5. The method for producing a glass material according to claim 1 or 2, wherein: The glass material further contains 0% to 40% of B2O3 and 5% to 100% of La2O3+B2O3 in mol%.
6. The method for producing a glass material according to claim 1 or 2, wherein: The β-OH value of the glass material shown in the following formula (1) is 0.005 mm -1 ~0.3mm -1 , (1) β-OH value = (1 / X) log (T1 / T2) X: Glass wall thickness (mm) T1: Reference wavelength 4000cm -1 Transmittance under (%) T2: Hydroxyl absorption wavelength 3300cm -1 ~3450cm -1 Minimum transmittance near (%).
7. The method for producing a glass material according to claim 1 or 2, wherein: The refractive index nd of the glass material is greater than or equal to 1.
85.
8. A glass material, characterized in that: Contains 5% to 75% La2O3 in mol%, The β-OH value shown in the following formula (1) is 0.005 mm -1 ~0.3mm -1 , β-OH value = (1 / X)log(T1 / T2) X: Glass wall thickness (mm) T1: Reference wavelength 4000cm -1 Transmittance under (%) T2: Hydroxyl absorption wavelength 3300cm -1 ~3450cm -1 Minimum transmittance near (%).
9. The glass material according to claim 8, wherein: The glass material is used in the visible light wavelength region.
Citation Information
Patent Citations
Optical glass, optical element and method for manufacturing optical glass
JP2014196236A